Further Evidence on the Asymmetric Behavior of Economic Time Series over the Business Cycle - Falk, Barry (Journal of Political Economy, 1986)
Evidence has recently been presented by Salih Neftçi to support the hypothesis that recessions in economic activity tend to be steeper and more short-lived than recoveries in economic activity. That evidence, however, was confined to the behavior of the unemployment rate in the United States. In this paper it is shown that when Neftçi's methods are applied to analyze the behavior of real gross national product, investment, and productivity in the United States or when they are used to analyze industrial production abroad, the asymmetry hypothesis seems to be less compelling.